1) y = (8x^6-4x^-3) ^-5 2) y=2 / (2-x^6) ^3

+1
Ответы (1)
  1. 11 июля, 04:15
    0
    Вычислим производные функций:

    1) y = (8 * x^6 - 4 * x^ (-3)) ^ (-5);

    y ' = ((8 * x^6 - 4 * x^ (-3)) ^ (-5)) ' = - 5 * (8 * x^6 - 4 * x^ (-3)) ^ (-5 - 1) * (8 * x^6 - 4 * x^ (-3)) ' = - 5 * (8 * x^6 - 4 * x^ (-3)) ^ (-6) * (8 * 6 * x^5 - 4 * (-3) * x^ (-4)) = - 5 * (8 * x^6 - 4 * x^ (-3)) ^ (-6) * (48 * x^5 + 12 * x^ (-4)) = - 5 * (48 * x^5 + 12 * x^ (-4)) / (8 * x^6 - 4 * x^ (-3)) ^6;

    2) y = 2 / (2 - x^6) ^3;

    y ' = (2 / (2 - x^6) ^3) ' = 2 * ((2 - x^6) ^ (-3)) ' = - 2 * 3 * (2 - x^6) ^ (-3 - 1) = - 6 * (2 - x^6) ^ (-4) = - 6 / (2 - x^6) ^4.
Знаешь ответ на этот вопрос?